The Incidence of Local Labor Demand Shocks - Notowidigdo, Matthew J. (Journal of Labor Economics, 2020)
Low-skill workers are comparatively immobile. This paper estimates the role of housing prices and social transfers in accounting for this fact using a spatial equilibrium model. Reduced-form estimates using US census data show that positive local labor demand shocks increase population more than negative shocks reduce population, that this asymmetry is larger for low-skill workers, and that such an asymmetry is absent for average wages, housing values, and rental prices. Generalized method of moments estimates reveal that the comparative immobility of low-skill workers is due not to higher mobility costs but to a lower incidence of adverse labor demand shocks.